1996
DOI: 10.1007/bf01254477
|View full text |Cite
|
Sign up to set email alerts
|

Phantom evaluation of simultaneous thallium-201/technetium-99m aquisition in single-photon emission tomography

Abstract: This study investigated downscatter effects in cardiac single-photon emission tomographic studies with simultaneous thallium-201/technetium-99m acquisition, and evaluated a previously proposed subtraction technique for downscatter compensation. Ten studies were carried out with different defect sizes and locations and varying activity distributions using four energy windows: 70+/-10% keV, 140+/-10% keV, 100+/-10% KeV, and 103+/-16% keV. The subtraction technique used the 100- or 103-keV data to remove scattere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The photons emitted during 201 Tl disintegration are mostly x-rays having a relatively broad energy spectrum. Moreover, the administration of a low dose of 201 Tl results in low counting rates and poor statistics compared with those of the other radioisotopes used in nuclear medicine (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photons emitted during 201 Tl disintegration are mostly x-rays having a relatively broad energy spectrum. Moreover, the administration of a low dose of 201 Tl results in low counting rates and poor statistics compared with those of the other radioisotopes used in nuclear medicine (14).…”
Section: Discussionmentioning
confidence: 99%
“…There are many different protocols for adjusting the energy windows in 201 Tl imaging (12)(13)(14)(15)(16)(17)(18), although commonly thallium images are acquired in 2 energy windows (11). The first energy window is set at the x-ray photopeak (68 6 10% or 68 6 15% keV), and the second window is set at the g-6 photopeak (167 6 20% keV).…”
mentioning
confidence: 99%
“…For example, 99m Tc photons emitted at 140 keV can be detected in the 201 Tl photopeak, centered around 72 keV, owing to energy loss in Compton scatter interactions or via the emission of lead X-rays from the collimator [4]. This down-scatter can lead to gross overestimation in activity and loss of contrast in small lesions [5,6,7,8]. For example, an irreversible defect (indicating non-viable tissue) in separate 99m Tc/ 201 Tl SPET can be interpreted as a reversible defect (indicating viable tissue) in DI-SPET, which may lead to needless angioplasty or bypass surgery, if down-scatter is not corrected for.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an irreversible defect (indicating non-viable tissue) in separate 99m Tc/ 201 Tl SPET can be interpreted as a reversible defect (indicating viable tissue) in DI-SPET, which may lead to needless angioplasty or bypass surgery, if down-scatter is not corrected for. In general, 99m Tc/ 201 Tl DI-SPET is often regarded as unsuitable for clinical use without adequate correction for the effects of down-scatter [2,5,8,9]. Several methods have been proposed to correct for down-scatter [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…While these methods lead to improvements in quantitation and contrast in the Tl image, they each have disadvantages similar to those associated with single-isotope scatter subtraction methods: each requires ad hoc determination of parameters such as scaling factors or blurring functions, the cross-talk estimate may not be accurate for all imaging situations, and the subtraction (or deconvolution) step is accompanied by a large increase in statistical noise. In a phantom evaluation by Cao et al (1996), subtraction-based crosstalk compensation methods were found to overestimate defect size and resulted in increased heterogeneity in the myocardial wall in some situations.…”
Section: Introductionmentioning
confidence: 99%